Making BABIWOR "Pork Carrot Meatballs" for Household Groups to Increase Entrepreneurship Opportunities - Achmadi, Puspita Cahya; Luju, Maria Tarsisia; Karlina, Maria Aprilliana Ade (International Journal of Community Service Learning, 2024)
Carrot pork meatballs (Babiwor) are a combination of animal and vegetable sources into a processed food product. Frozen food pork carrot meatballs are one of the product innovations that can extend the shelf life of products and are able to meet the tastes of people and their surroundings who believe in non-Muslims. PKM activities consist of 3 series, namely location survey, outreach and training. The aim of socialization and training activities on making Babiwor directly targeting housewives as the main target is to increase the level of innovation, creativity, reduce unemployment rates, and fulfill animal and vegetable nutritional needs. And can increase the value of economic welfare. Through community service activities, new economic business alternatives can be provided in the community. This type of research is descriptive qualitative. The subjects involved in this research were housewives. The data collection methods used are observation and mapping or field measurements. The instrument used is a survey form or questionnaire. The data analysis used is descriptive analysis. The main results of the research obtained were significant results, after carrying out the community service program, participants were able to process pork into carrot pork meatballs. The implication of this research is that it can make a real contribution to improving production skills and culinary innovation for household groups, so that they are better prepared to compete in the processed food market.